Regional variation in percutaneous absorption in in vitro human models: a systematic review. (3rd April 2022) - Feschuk, Aileen M.; Kashetsky, Nadia; Chiang, Chavy; Burli, Anuk; Burdick, Halie; Maibach, Howard I.
ABSTRACT: Percutaneous absorption is of importance given its role in topical medicaments, transdermal drug systems, and dermatotoxicology. Many factors influence percutaneous penetration, including anatomical region, although little is currently known regarding this parameter. Hence, the aim of this study was to summarize existing data on regional variation in percutaneous penetration in in vitro human models. PubMed, Embase, Web of Science, and US patent literature were explored, and relevant data collected. Eight eligible articles were identified, which together, explored 15 anatomical locations. Four investigations compared percutaneous penetration between scalp and abdominal skin, and all concluded that the former was more permeable. Within those four studies, 10 penetrants of varying physical/chemical properties were tested indicating that in those particular study conditions, anatomical location exerted a greater effect on percutaneous absorption than the physicochemical properties of the penetrants. In addition, torso area was less absorptive than scrotum in both studies in which these sites were compared. In conclusion, the scrotum and scalp appear to be highly susceptible to percutaneous absorption compared to other locations such as the abdomen. This is postulated to be largely due to the high density of hair follicles in these areas, enabling greater penetration via the appendageal pathway. However, there is a paucity of conclusive data regarding the penetrability of other anatomical locations. Investigations testing and ranking the susceptibility of different anatomical regions is of vital importance given the importance of (1) transdermal drug delivery and decontamination protocols and (2) understanding the underlying mechanisms and degree of these variances might aid our pharmacologic/toxicologic judgments.